Distúrbios miofuncionais orofaciais em pacientes diagosticados com a anemia falciforme na F. HEMOAM - Amazonas - Pinheiro, Lidiane de Sousa (2023)
Sickle cell anemia is the most common genetic hemoglobinopathy worldwide, characterized by hemoglobin S, which causes sickling of red blood cells, resulting in chronic hemolytic anemia, obstruction of blood vessels with pain attacks, infarction and necrosis of organs and systems, including the hard and soft tissues of the stomatognathic system. Objective: To investigate orofacial myofunctional disorders in patients diagnosed with sickle cell anemia. Methodology: This is a descriptive, observational and cross-sectional study. Patients of both genders were studied, diagnosed with sickle cell anemia aged from 6 years to 71 years, who were undergoing medical treatment at the Fundação Hospitalar de Hematologia e Hemoterapia do Amazonas. Syndromic patients, or those undergoing head and/or neck surgery, were excluded; with nasal enteral tube and/or tracheostomy; with congenital or acquired osteodental changes. After contact and signing of the Terms of Consent and Assent, the Clinical/Epidemiological Profile was drawn up and the Orofacial Myofunctional Assessment Protocol with Scores was applied to 90 patients. Results: The measurement of the patients' interincisal oral opening presented an average of 34.08 mm ±7.4 mm. The level of prevalence of dysfunction was considered when 30 patients or more presented functional changes. The study demonstrates dysfunction in tongue mobility regarding elevation in 37.78% of patients and 33.33% of patients presented dysfunction in protrusion. Conclusions: It was found that the measurement of interincisal oral opening is below the standards cited in the literature, tongue mobility presents inaccuracy in elevation and protrusion. This can be justified by probable changes in blood flow that sickle cell anemia can promote.